Essential Knowledge to Impart to Young Women about the Specifics of Human Sexuality/ Reproduction - Pierre-Yves, Robillard (British Journal of Healthcare and Medical Research, 2023)
Homo sapiens appeared some 300,000 years ago and our female ancestors delivered obligatorily vaginally prior to the development of medical interventions (such as caesarean sections, a safe procedure only since the 1960’s). Furthermore, women are unique among the 4,300 mammal species suffer from a harmful complication of pregnancy, preeclampsia (especially during a first pregnancy). This paper explains first, concerning physiological vaginal first birth (primiparity) why young women should consider delivering her first baby before the age of 26 (there is a linear association between maternal ages and healthy deliveries). Second, because of the comparatively large human fetal brain, nutritional maternal-foetal exchanges are twice those of other mammals (per body-mass ratios). But, as the human species has retained the hemochorial placenta, that first appeared in mammalian evolution, women face the great challenge of immunological tolerance towards the male partner’s tissues during the nine months of gestation. This major challenge occurs during the first pregnancy and tolerance is related to semen exposure prior to conception. In subsequent additional pregnancies, immunological recognition is largely achieved through the initial pregnancy. This is why for a first pregnancy (nulliparous woman or multiparous woman with a new male partner), it is preferable to conceive after a delay of 6 months of non-barrier contraception before planning conception. In case of short sexual cohabitation since the constitution of the couple (partial recognition of the male’s tissue), implantation of the embryo may be partially insufficient, leading to complications such as fetal growth restriction and/or early onset preeclampsia. Third, to have a baby neither too small, nor too big, women overweight or obese at the beginning of any pregnancy must gain less weight during the 9 months of gestation as compared to their leaner counterparts. The optimal gestational weight gain may be acknowledged during the first prenatal visit, with, a goal to achieve during the next 7- 8 months of pregnancy.